Implementation of Project-Based Learning to Build Student Character and Pancasila Values ​​at Al-Ma'arif Islamic Middle School, Prapen - Baiq Intan Setiawati Rinjani; Anggun Febriyanti; Roni Santuri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research was carried out against the background of the importance of implementing project-based learning to build student character and Pancasila values at Al Ma'arif Prapen Islamic Middle School. This research aims to determine the implementation of project-based learning to build student character and Pancasila values at Al Ma'arif Prapen Islamic Middle School. This research uses a qualitative descriptive method, with data collection through interviews, observation and documentation. The subjects of this research were PPKn teachers and students at Al Ma'arif Prapen Islamic Middle School. The results of this research show that the implementation of project-based learning consists of several aspects, namely; (1) Project-based learning can build character based on Pancasila values in students, (2) Effective strategies for project-based learning in building student character based on Pancasila values, (3) Teacher challenges in applying learning methods to build character according to values Pancasila values.